Integrated Approach of Retrofitting an Existing Residential Building to a Nearly Zero Energy Building with Simultaneous Seismic Upgrading - Pamboris, George; Chrysostomou, Christis; Kalogirou, Soteris A.; Christodoulides, Paul (My University, 2024)
Introduction: The current study's goal is to apply an integrated approach of retrofitting a typical building in Cyprus that was designed and constructed for the refugee settlements in the period 1975-1985. The existing building is retrofitted to a nearly zero-energy building. Methods: This typical type of building examined represents approximately 15,347 houses and stands for 3.57% of households in Cyprus. This percentage is considered significant with regards to energy consumption, as this type of structure has an estimated energy consumption of 1000 kWh/m2/y and CO2 emissions of 293.74kg CO2/m2/y. This corresponds to 0.293 Mt CO2/y, which stands for 4.18% of total CO2 emissions in Cyprus for 2011, based on the latest IEA (International Energy Agency) data. An integrated approach is followed for the retrofitting of the existing building, which involves both energy and structural upgrades, taking into account the earthquake resistance upgrade. Since Cyprus is in a highly seismic region, an important factor in this approach is the ability of the structure to survive a strong earthquake during its remaining lifetime, according to the design criteria. The study presents and discusses three possible coalitions with multiple scenarios of approaching the upgrade of the existing building. In each coalition, various criteria and implementation actions are considered based on the energy consumption, the CO2 footprint, and the seismic resistance. Results: The study also investigates whether the extension of life expectancy of the existing structure through earthquake resistance upgrade will have a positive or negative effect on the CO2 life cycle footprint and cost of the building. Results show that for the examined typical building, simultaneous energy and earthquake resistance upgrade is more efficient in terms of cost and environmental impact. The building with the smallest construction age had the smallest Decision-Making Index (DMI) from the A, B and C coalitions. Conclusion: It is important that for an existing building, the option to remain in its original state (coalition A) without any upgrading intervention is not the most favorable option. Therefore, the need to evaluate the existing building stock and plan the upgrade of the buildings in question is of utmost importance.
Keywords: Building; Seismic upgrading; Nearly zero energy building; Life cycle; CO2 footprint; Seismic retrofitting